The Effect of Stick Box Portable Game to Increase Basic Mathematics Ability Children Five to Six Age (Study Eksperimen in Aisyiyah Bustanul Athfal Kindergarten Kaliwungu) - Maghfiroh, Oktari Wulan; Diana, Diana (Jurusan PGPAUD FIP UNNES, 2016)
Mathematic is important ability to be taught by teacher to kindergarten children so that they have skill in solving simple problems in modern technology. Introduction of basic mathematics concept should be given from an five to six age. Stick box portable game is One of the way to develop basic mathematics to children. The purpose of the research was to determine the effectiveness of the Stick box portable game as the introduction of the concept basic mathematics from an five to six age children in Aisyiyah Bustanul Athfal kindergarten. This research uses experimental methods of Posttest Only Control Design. Using a Purposive random sampling. Elected to the Aisyiyah Bustanul Athfal Kindergarten 3 SarirejoÂ (experimentation) and Aisyiyah Bustanul Athfal Kindergarten 6 Kutoharjo (control). Based on t-test data Independent t-test results data control group and experimental group was significant because it has the value t calculate=-5,511 with Sig (2-tailed) 0.00<0.05. Introduction of basic mathematics concept mean in children there is a significant difference between the experimental and control groups.